Prediction of long-term behaviour of composite materials - Rui Miranda Guedes (2000)
After a brief introduction, where the question of durability related to composite materials is raised concerning the type of applications and the constituents of the composite material, some considerations are given about the interaction between physical and chemical ageing and its effect on the long-term behaviour of those materials. A comparison of different methodologies to define models for the constitutive laws of the material is made, together with a reference to methodologies used for real structures in order to predict long-term behaviour. An algorithm to predict long-term laminate properties of fibre reinforced composites is presented. In the procedure, the classical laminate plate theory was extended to include time-related response of composite materials for membrane and bending load. An efficient semi-direct time integration scheme, providing a stable integration process, was derived to be included in the numerical procedure. The present formulation enables solving problems related with creep, stress relaxation and rate dependent stress-strain behaviour for in-plane and bending loads. The results concerning studies related to the influence of water and temperature on the long-term behaviour of fibre reinforced composite, hence on the constitutive models, are presented. The experimental results shows that a combined time-temperature-moisture superposition principle (TTMSP) is not valid. This principle simply states that the effects of temperature and moisture on the viscoelastic properties can be uncoupled.